Safe recovery after cesarean in rural Africa: Technical consensus guidelines for post-discharge care - Kateera, Fredrick; Gauthier, Bethany Hedt; Luo, Amy; Niyigena, Anne; Galvin, Grace; Hakizimana, Sadoscar; Molina, Rose L.; Boatin, Adeline A.; Kasonde, Prisca; Musabeyezu, Juliet; Ngonzi, Joseph; Riviello, Robert; et al. (International Journal of Gynecology & Obstetrics, 2022)
Despite increasing cesarean rates in Africa, there remain extensive gaps in the standard provision of care after cesarean birth. We present recommendations for discharge instructions to be provided to women following cesarean delivery in Rwanda, particularly rural Rwanda, and with consideration of adaptable guidelines for sub-Saharan Africa, to support recovery during the postpartum period. These guidelines were developed by a Technical Advisory Group comprised of clinical, program, policy, and research experts with extensive knowledge of cesarean care in Africa. The final instructions delineate between normal and abnormal recovery symptoms and advise when to seek care. The instructions align with global postpartum care guidelines, with additional emphasis on care practices more common in the region and address barriers that women delivering via cesarean may encounter in Africa. The recommended timeline of postpartum visits and visit activities reflect the World Health Organization protocols and provide additional activities to support women who give birth via cesarean. These guidelines aim to standardize communication with women at the time of discharge after cesarean birth in Africa, with the goal of improved confidence and clinical outcomes among these individuals.
Keywords: Global surgery; Maternal health; Postpartum; Rwanda; Sub-Saharan Africa